Pengaruh Profitabilitas, Leverage, Dan Tax Planning Terhadap Manajemen Laba Dengan Komite Audit Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaaan Sektor Industri Makanan Dan Minuman Yang Terdaftar Bei Periode 2018–2022) - Mahdiyah Septiani Larasati; Bambang Subiyanto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to analyze and obtain empirical evidence of the influence of profitability, leverage, and tax planning on earnings management with the audit committee as a moderating variable in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This study used multiple regression linear data analysis techniques and moderated regression analysis (MRA) using SPSS program version 25. The sample used was purposive sampling of 15 companies and obtained 75 data. Based on data analysis, it is stated that profitability and tax planning have a positive effect on earning management, Audit committees can weaken or strengthen profitability, leverage and tax planning on earnings management. Keywords: Profitability; Leverage; Tax Planning; earning management; Audit committee